(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The objective of this work was to analyze, from an anthropological and feminist perspective, the circus performance Hendiduras, held in 2022 at the National University of San Martín in Buenos Aires, Argentina, as a degree thesis in Performing Arts focused on Circo por Victoria. Marecos and his women’s acro-duo troupe. I intended to explore the dimensions of kinesthesia, corporality, affects and performance as producers of embodied and gendered knowledge that twist heterosexual codes in two interrelated aspects: in the hegemonic acro-duo circus technique that assigns the cisgender man the role of "strong" or "portor" and the woman of "volante"; and in the scenic space of the circus, making appear collective and innovative and dissonant ways of dramatizing femininity in the circus. Finally, I cross-linked the scenic piece with the broader context of effervescence of the feminist movement of which it is a part.